Amish outsider - Perry, Marta (Perry, Marta. River Haven, 2019)
"In the wake of his estranged wife's murder, widower Michael Forster returns to the Amish community he'd left as a teen. He wants a fresh start for himself and his daughter, Allie, away from those who still believe he's guilty. In River Haven, a quieter life seems possible. If only Allie's Amish schoolteacher, Catherine Brandt, was easier to ignore. A problem solver by nature, Cathy can tell Allie's withdrawn demeanor isn't due to shyness. But getting through to Allie also means breaching her father's hardened defenses. What starts as persistence soon grows into an attraction neither Cathy nor Michael saw coming. When the past suddenly threatens both his daughter and the woman he loves, Michael must risk everything to save them"--FantasticFiction.com.